Post-fire regeneration of cork oak (Quercus suber) in Kiadi forest (Akfadou- Algeria) - Dib, Tassadit; Kazanis, Dimitrios; Arianoutsou, Margarita; Messaoudene, Mahand; Krouchi, Fazia (Mediterranean Botany, 2022)
Cork oak (Quercus suber) as a West Mediterranean species is known for its ecological, economic and social values. Wildfires are one of the most serious problems threatening Quercus suber, endangering its occurrence in its area of distribution. Therefore, knowing the behavior of the species after fire and the factors influencing its responses are particularly important for forest management. In this study we assessed the post fire vegetative recovery in 730 trees affected by wildfires on 2014 in Kiadi cork oak forest, located in the Western side of Akfadou Mountains in Algeria. Few months after the fire, individual tree mortality was very low (7.53%), and nearly, all the trees sampled survived the fire since almost all trees resprouted from canopy and some of them showed basal resprouts. Moreover, those two modes of post fire vegetative recovery were not correlated to each other. The performed redundancy analyzes (RDA) revealed that the cork oak post-fire response was highly correlated with individual characteristics and with the environmental data. The main variables influencing the likelihood of good or poor vegetative recovery were the understory height and cover, soil characteristics, fire severity, tree status (alive/dead trees), tree diameter and tree exploitation. Our results confirmed the fire resistance of cork oak species; which is also the only Algerian tree to resprouts. Hence, this makes the species a good candidate for reforestation programs in fire prone ecosystems.